Language and Identity in Sandra Cisneros’s The House on Mango Street - Veras (UFRGS), Adriane Ferreira (ANTARES: Letras e Humanidades, 2011)
This article presents a critical reading of the novel The House on Mango Street by the Chicana author, Sandra Cisneros. The focus of the reading falls on Esperanza, the novel narrator, and her longing for a home as a representation of her need to self-affirm and develop her identity. This paper analyses the identity issue of a subject culturally hybrid, besides that, it also analyses aspects of the narrative, including language as a mark of such identity. The novel can be considered a representative of a Chicano discourse, in which one can follow Esperanza's journey of growth and development into the adult life, constituting a Chicano Bildungsroman. The theoretical support used comprehends authors who investigate identity issues, such as Stuart Hall, Homi Bhabha and Gloria Anzaldúa.